Tantangan Sekularisme terhadap Identitas Kaum Muda Katolik di Era Modern dan Implikasinya bagi Pendidikan Agama - Jawan, Fransiska Masandai; Monica Innanda Chiaralazzo; Intansakti Pius X (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The development of globalization, digital technology, and social change has influenced the way young people understand and live out their faith. Secularism tends to place religion in the private sphere, so that religious values do not always become the basis for decision-making in daily life. This study aims to analyze the challenges of secularism to the formation of the identity of Catholic youth in the modern era and to formulate relevant religious education responses in addressing these dynamics. This research uses a qualitative approach with a literature study method that examines various scientific literature, Church documents, and research findings related to the phenomenon of secularism and the formation of the religious identity of Catholic youth. The results of the study indicate that secularism has a complex impact on the faith life of young people, including decreased participation in Church activities, the emergence of individualistic attitudes, and the tendency to view religion merely as a formal identity. However, on the other hand, the modern era also opens opportunities for young people to develop their faith creatively through the use of digital technology and involvement in faith communities. Therefore, Catholic religious education and pastoral accompaniment that are dialogical, contextual, and participatory are very important in helping Catholic youth integrate their faith into daily life. This study is expected to provide theoretical and practical contributions for educators and pastoral ministers in fostering the faith identity of Catholic youth in modern society.